Upaya Meningkatkan Hasil Belajar PKn Dengan Menerapkan Model Pembelajaran Mnemonic - Guntur Siahaan (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This research is conducted as an effort to improve learning outcomes with the model of learning Mnemonic on the subject of civic education material role of Indonesian foreign policy. Subjects in this study were students of grade VI SDN 014676 Silau Maraja district Setia Janji academic year 2016/2017. Learning process after learning result using Mnemonic learning model in cycle I reaches average value 79.18 with classical learning completeness equal to 60%. Learning outcomes in cycle II reached an average grade of 89.4 with 90% complete classical learning. It can be concluded that there is an increase in learning outcomes with the model of learning Mnemonic on the subject matter civic education role of Indonesian foreign policy on students of class VI SDN 014676 Silau Maraja district Setia Janji academic year 2016/2017. Keywords: mnemonic, foreign policy Abstrak: Penelitian ini dilakukan sebagai upaya meningkatkan hasil belajar dengan model pembelajaran Mnemonic pada pelajaran PKn materi peranan politik luar negeri Indonesia. Subjek dalam penelitian ini adalah siswa kelas VI SDN 014676 Silau Maraja kec. Setia Janji TP. 2016/2017. Hasil proses belajar setelah pembelajaran menggunakan model pembelajaran Mnemonic pada siklus I mencapai nilai rata-rata 79,18 dengan ketuntasan belajar klasikal sebesar 60%. Hasil belajar pada siklus II mencapai nilai rata-rata 89,4 dengan ketuntasan belajar klasikal sebesar 90%. Dapat disimpulkan bahwa terjadi peningkatan hasil belajar dengan model pembelajaran Mnemonic pada pelajaran PKn materi peranan politik luar negeri Indonesia pada siswa kelas VI SDN 014676 Silau Maraja kec. Setia Janji TP. 2016/2017. Kata kunci: mnemonic, politik luar negeri